Effectiveness of Yoga versus Exercise for Reducing Falling Risk in Older Adults: Physical and Psychological Indices. Issue 4 (August 2022) - Bartos, Luis J.; Meek, Geoffrey A.; Berger, Bonnie G.
Our purpose in this study was to examine the effectiveness of yoga to address multiple risk factors of falling in active and low active older adults. Community–dwelling older adults ( N = 35) over the age of 65 actively participated in either a yoga program, an exercise program, or a no–program control. Participants completed measures associated with falling risks. Physical measures included lower body strength, static balance, and lower body flexibility. Psychological measures included perceived self-efficacy with respect to falls and health–related quality of life. We determined between–group differences using planned comparisons, effect size, confidence intervals, and probability of superiority. Results of planned comparisons and practical significance testing indicated that yoga participants scored higher than the exercise and control participants on both right and left lower body flexibility tests. Yoga participants also scored higher than the control participants on right leg static balance, and the right and left lower body flexibility tests. The exercise participants scored higher than yoga participants on the RAND-36 Quality of Life subscales of Energy/Fatigue, Pain, and General Health. The probability of superiority results indicated that the no–program older adult participants would benefit by enrolling in the yoga rather than the exercise program to reduce physical risks of falling. These findings were discussed in relation to promoting physical activity programs to reduce risks of falling, and the roles of the protocol, practical significance, and measures employed when determining program effectiveness.